(untitled) - Farrell, Thomas S. C. (London, 2010)
Offering a practical, research-based introduction to first and second language acquisition, this guide to English language teaching presumes no prior knowledge of linguistics or language education. The new edition includes two additional chapters covering technology and how reflective teaching practices support CLT-based activities, case studies to consolidate theory and demonstrate best practice and updated real world examples, drawing on teaching experiences from North America, Africa and Asia. Taking a 'big picture' view of second language learning and teaching, this is an energising and fun resource for language practitioners"
Keywords: English language; Study and teaching,Foreign speakers